Addition of Lavender Essential Oil (Lavandula angustifolia) in Manufacture Baby Products Diaper Rash Cream - Nurina Ade Almira; Nanda Mila Afida; Kun Harismah (Urecol Journal. Part D: Applied Sciences, 2022)
Essential oils are known by the name of ethereal oil or flying oil (ethereal oil or volatile oil ) which is produced by plants. At high concentrations, essential oils can be used as local anesthetics. Essential oils have strong antibacterial and antifungal properties, one of which is lavender essential oil which has commercial relevance in pharmaceutical applications due to its therapeutic properties, such as anticonvulsive, sedative, antidepressant, antiseptic, antihypertensive, antioxidant, and anti-inflammatory. Not only lavender essential oil, coconut oil or commonly known as VCO is an oil that contains vitamin E that the skin needs and is medically useful for healing cracked skin. Coconut oil or VCO is rich in antibacterial, antiaging, antioxidant, wound healing, and anti-inflammatory properties. Pharmaceutical applications that are very important for humans are antioxidant, anti-inflammatory and antibacterial, especially for babies. Infants are an extreme age group who are at risk of damage to skin integrity in the perianal area. This can be due to factors such as increased humidity causing a rash. The purpose of this study was to determine the benefits of using lavender essential oil using coconut oil VCO in the manufacture of baby diaper rash cream products to prevent skin integrity in infants such as rashes. The method used in this study is a qualitative descriptive analysis test. Where using testing 5 times on 4 samples, it was proven that the 4th sample had a good level of characteristics. The results of this study, the test was proven by organoleptic testing carried out, namely the color produced was white, the aroma was lavender, and it had a creamy texture. Homogeneity test has homogeneous results. The pH test resulted in 7.84. The stickiness test on the 4th sample lasted for 1 minute 10 seconds. The dispersion test with a load of 50 grams is 2 cm, a load of 100 grams is 3.7 cm, a load of 150 grams is 4 cm, a load of 200 grams is 4.2 cm, and a load of 250 grams is 4.5 cm.